base study and source of shahnameh advices - sajjad rahmatian; esmat khoeini (متن شناسی ادب فارسی, 2015)
Attention to the advice and advicing in Iran has a life to the length of history, so that in the middle of oldest writing remainder from ancient Iran one can see the presence advices and councels.Â This tradition continued in the Islamic period and has continued its existence until our time and in this way, almost long, many of Iranian grandee and literateurs turned in and in this relation have lef precious works from themselves.Â One of the greatest poets of persian literature that have a special attention to the advice and counsel subject is Abolqasem e Ferdowsi. He in Shahnameh accorded special status for advice and counsel, and has been left in this aspect pithy and eloquent lines which from long time ago welcomed by public, and of course this is apart from numerous advices than there are in the text of the Shahnameh stories and expressed from characters language. This research more than anything else tries to reveal intellectual sources of some Shahnameh advices and are presented in this base, more than Pahlavi books and andarzname like: Azarbad e Marspandan advices, andarzname Bozorgmehr, javidan e kharad, and poetry more poet before Ferdowsi like Rudaki as effective sources on Shshnameh advices.